2002
DOI: 10.1086/343054
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ANKH Cause Chondrocalcinosis

Abstract: Chondrocalcinosis (CC) is a common cause of joint pain and arthritis that is caused by the deposition of calcium-containing crystals within articular cartilage. Although most cases are sporadic, rare familial forms have been linked to human chromosomes 8 (CCAL1) or 5p (CCAL2) (Baldwin et al. 1995; Hughes et al. 1995; Andrew et al. 1999). Here, we show that two previously described families with CCAL2 have mutations in the human homolog of the mouse progressive ankylosis gene (ANKH). One of the human mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
2
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 23 publications
6
151
2
8
Order By: Relevance
“…Interestingly, these genes included Dmp1, Ank, and Enpp1, all of which are known to play key roles in the process of extracellular matrix mineralization not only in mice but also in humans. (35)(36)(37)(38)(39)(40)(41)(42)(43) Moreover, since we observed that, at least relative to Alpl, all three genes were expressed at lower levels in Mdk-deficient osteoblasts, it is reasonable to speculate that these results provide a molecular explanation for the skeletal phenotype of Mdk-deficient mice. As discussed below, this is particularly true for Ank and Enpp1, whereas the decreased expression of Dmp1 rather should result in other abnormalities.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, these genes included Dmp1, Ank, and Enpp1, all of which are known to play key roles in the process of extracellular matrix mineralization not only in mice but also in humans. (35)(36)(37)(38)(39)(40)(41)(42)(43) Moreover, since we observed that, at least relative to Alpl, all three genes were expressed at lower levels in Mdk-deficient osteoblasts, it is reasonable to speculate that these results provide a molecular explanation for the skeletal phenotype of Mdk-deficient mice. As discussed below, this is particularly true for Ank and Enpp1, whereas the decreased expression of Dmp1 rather should result in other abnormalities.…”
Section: Discussionmentioning
confidence: 71%
“…playing a role in the regulation of extracellular matrix mineralization in mice and humans. (36)(37)(38)(39)(40)(41)(42)(43) In contrast, Mdk did not affect the expression of other osteoblast marker genes, such as Ibsp (encoding bone sialoprotein), Alpl (encoding tissuenonspecific alkaline phosphatase), and Bglap (encoding osteocalcin). To confirm these data, we next performed quantitative RT-PCR using independently isolated cultures and found a significant induction of Dmp1, Ank, and Enpp1 expression following Mdk administration, whereas expression of Alpl was reduced significantly (Fig.…”
Section: Increased Cortical Bone Resorption In Aged Mdk-deficient Micementioning
confidence: 94%
“…In mice, loss-offunction mutations of Ank lead to arthritis, ectopic crystal formation, and generalized joint fusion, (51) whereas, in humans, dominant mutations are associated with craniometaphyseal dysplasia (52,53) and familial chondrocalcinosis. (54,55) Thus, like Enpp1, decreased Ank expression in the spinal tissues of ENT1 -/-mice would be expected to further suppress extracellular PP i levels, permitting the formation of ectopic mineral deposits.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pyrophosphate transporter, so presumably the source of the pyrophosphate is intracellular although the biochemical pathway is unknown. Mutations in its human homolog, ANKH, cause a group of diseases including craniometaphysial dysplasia and chondrocalcinosis [Reichenberger et al, 2001;Nurnberg et al, 2001;Williams et al, 2002;Pendleton et al, 2002].…”
Section: Equationmentioning
confidence: 99%